2003
DOI: 10.1016/s0304-3959(03)00227-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential utility of the peripheral analgesic properties of morphine in stomatitis-related pain: a pilot study

Abstract: To determine the potential clinical utility of peripheral opioid action using a clinical model of cancer treatment-induced inflammation and pain that allowed for topical application of morphine in the damaged tissue (oral mucosa). This pilot study followed a two blocks design. Ten patients with painful oral mucositis were enrolled in the first block (dose-response relationship finding) and randomized in two groups to receive oral rinses with 15 ml of either 1 per thousand or 2 per thousand morphine solution. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 41 publications
0
58
1
2
Order By: Relevance
“…A case series reported that the topical administration of a 0.08 % morphine gel provided pain relief in six cases of either cutaneous or oral mucosal pain [51]. Two studies, including a RCT, examined the use of a 2 % morphine mouth rinse for the management of pain due to OM in patients receiving chemoradiation for H&N cancer [21,22]. In the RCT, morphine mouth rinse was compared to a "magic mouthwash" containing lidocaine, diphenhydramine, and magnesium aluminum hydroxide.…”
Section: Topical Morphinementioning
confidence: 99%
“…A case series reported that the topical administration of a 0.08 % morphine gel provided pain relief in six cases of either cutaneous or oral mucosal pain [51]. Two studies, including a RCT, examined the use of a 2 % morphine mouth rinse for the management of pain due to OM in patients receiving chemoradiation for H&N cancer [21,22]. In the RCT, morphine mouth rinse was compared to a "magic mouthwash" containing lidocaine, diphenhydramine, and magnesium aluminum hydroxide.…”
Section: Topical Morphinementioning
confidence: 99%
“…Only three studies were identified that systematically evaluated these mouthwashes, two of which studied prevention [4,20] and one of which studied treatment of OM [8]. Levels of evidence were IV, III, and IV, respectively, and the results were conflicting.…”
Section: Mixed Medication Mouthwashmentioning
confidence: 99%
“…5,22 To control the nociceptive pain component of oral pain associated with mucositis, the potential utility of local topical application of opioids, such as a mouthwash containing 2% morphine, has been proposed. 63 However, the mainstay of analgesic therapy for oral pain associated with OM is the parenteral administration of opioids. For this purpose, tramadol is useful in the control of mild to moderate pain.…”
Section: Loading Dosementioning
confidence: 99%